2017
DOI: 10.1001/jamaophthalmol.2017.4574
|View full text |Cite
|
Sign up to set email alerts
|

Development of an 18-Item Measure of Symptom Burden in Patients With Glaucoma From the Collaborative Initial Glaucoma Treatment Study’s Symptom and Health Problem Checklist

Abstract: IMPORTANCE Administration of a brief questionnaire to evaluate glaucoma symptoms would lend useful information for patient care.OBJECTIVES To develop a shortened glaucoma symptom measure based on the Collaborative Initial Glaucoma Treatment Study (CIGTS) Symptom and Health Problem Checklist (SHPC) and evaluate its psychometric properties. DESIGN, SETTING, AND PARTICIPANTSThis measure development study evaluated the factor structure of the 43-item SHPC that was obtained from CIGTS participants at baseline and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…due to a possible social stigma). Nevertheless, other studies have demonstrated the reliability of patient-reporting (Hosseini et al, 2018;Musch et al, 2018).…”
Section: Study Limitations and Strengthsmentioning
confidence: 98%
“…due to a possible social stigma). Nevertheless, other studies have demonstrated the reliability of patient-reporting (Hosseini et al, 2018;Musch et al, 2018).…”
Section: Study Limitations and Strengthsmentioning
confidence: 98%
“…Ultimately, 64 publications and 7 reviews (71 publications) were identified from the literature relating to 41 different QoL questionnaires (general health, vision-specific and glaucoma-specific questionnaires) which were included in the qualitative analysis (see Table, Supplemental Digital Content 3, which lists the 41 QoL questionnaires included in the analysis, http://links.lww.com/IJG/A562). 15,28–81…”
Section: Resultsmentioning
confidence: 99%
“…86 Other questionnaires such as the Glaucoma Satisfaction Questionnaire (Glausat) and the Symptom Health Problem Checklist (SHPC) were identified as interesting options and were thoroughly considered but were subsequently excluded from the top 10 questionnaires because of either a lack of evidence or no availability in English language. The SHCP, an 18-item version of the SIG [which consisted of 43 items, 4-domain tool, in the Collaborative Initial Glaucoma Treatment Study (CIGTS)] proposed by Musch et al, 68 was able to differentiate between disease severity on local eye and visual function (P < 0.05) and that patients who underwent trabeculectomy reported higher frequency of local eye symptoms than those with topical medications (P < 0.01). However, it should be tested in other clinical settings to demonstrate its general applicability.…”
Section: Discussionmentioning
confidence: 99%